2012
DOI: 10.5152/balkanmedj.2012.021
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Complications Due to Subacute Suppurative Otitis Media

Abstract: Subacute otitis media is a well-known pathology of ENT practice which is easily diagnosed and subsequently treated in the outpatient clinic. The rate of complications in acute otitis media is lower than in chronic otitis media. We present here the history of a young patient with subacute otitis media who developed both localized labyrinthitis and facial palsy requiring surgical treatment. We conclude that the treatment of subacute otitis media should be carefully monitored because complications may occur. Surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, there are very few cases in the literature regarding multiple complications occurring concomitantly in the same case [3][4][5] . For instance, Berçin et al [5] reported a case with facial nerve paralysis, lateral sinus thrombosis, and sensorineural hearing loss, Qirjazi et al [3] discussed a case with facial palsy and serous labryrinthitis due to subacute otitis media, and Saffer et al [6] reported a seven-year-old boy with lateral sinus thrombosis and cervical abscess secondary to cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are very few cases in the literature regarding multiple complications occurring concomitantly in the same case [3][4][5] . For instance, Berçin et al [5] reported a case with facial nerve paralysis, lateral sinus thrombosis, and sensorineural hearing loss, Qirjazi et al [3] discussed a case with facial palsy and serous labryrinthitis due to subacute otitis media, and Saffer et al [6] reported a seven-year-old boy with lateral sinus thrombosis and cervical abscess secondary to cholesteatoma.…”
Section: Discussionmentioning
confidence: 99%